Comparison of the TruView PCD video laryngoscope and macintosh laryngoscope for pediatric tracheal intubation by novice paramedics: a randomized crossover simulation trial - Szarpak, Łukasz (Eur J Pediatr, 2015)
The aim of the present study was to evaluate whether the TruView video laryngoscope (TruView) facilitates pediatric endotracheal intubation (ETI) more quickly and safely than conventional Macintosh laryngoscope (MAC) in three manikin-based airway scenarios. This was a randomized crossover manikin study including 120 novice paramedics. The participants performed tracheal intubations using both TruView and MAC on a pediatric manikin in a control scenario (A), chest compression scenario (B), and chest compression cervical stabilization scenario (C). The sequence of scenarios was randomized. The primary outcome was time to intubation. Secondary outcomes were overall success rates, incidence of dental trauma, and ease of intubation. All intubation attempts were assessed by a trained assistant. The overall success rate was significantly higher with the TruView compared than the MAC in scenario B (100 vs. 81.7 %; p = 0.011) and scenario C (100 vs. 68.3 %; p < 0.001). The intubation time was significantly lower with the TruView than the MAC (18.5 vs. 24.3 s, p = 0.017, for scenario A; 21.6 vs. 25.7 s, p = 0.023, for scenario B; and 28.9 vs. 45.4 s, p < 0.001, for scenario C). Glottic view quality was better with TruView than the MAC in all scenarios, p < 0.001. Conclusions: The TruView offers better intubation conditions than the MAC on a pediatric manikin in the control scenario, chest compression scenario, and chest compression scenario with cervical stabilization scenario. The TruView may be used to elevate the epiglottis for orotracheal intubation. Further clinical studies are necessary to confirm these initial positive findings. Trial Registration: clinicaltrials.gov Identifier: NCT02289872.